Novos mediadores e articulação política no campo: a lógica do protagonismo social e o uso da pobreza - Lima, Jânison Pereira (2013)
The study elucidates the role of articulation in Semiarid (ASA) and the Centro Dom José Brandão de Castro (CDJBC), responsible for the realization of public politics that drive changes in rural semiarid of Sergipe. These organizations are understood as ´New Mediators´, which emerge on the scene of political articulation in the context in which the State reduces its role in supporting social demands. The methodological surpassed the understanding of the current context of capitalist relations and the State, which gives way the actions of new mediators, the time you transfer a certain kind of role for civil society. Reflected further on the nature of civil society, the third sector and poverty, inserted into the specifics of their adaptations to the operating logic of public policy, within the totality of relations. Poverty, in that direction, it is assumed as the scope of policies that establish in the field, taking a new direction in Brazil, from the 1990s due to the detriment of the debate around the generating causes of social inequalities. One change that meets the aspirations of capitalist relations, that legitimizes the public-private relationships in the implementation of actions for poor communities. Were also carried out a field research in rural communities supported by the actions of those mediators. The results point to a kind of principal role of public and private agents and, also population, without guidance for a process of emancipation in rural areas.